ICD-10 a comprehensive guide : education, planning, and implementation - Dalgleish, Carline A. (Clifton Park, New York : Delmar Cengage Learning, 2013)
"ICD-10: A Comprehensive Guide fully prepares current and future medical coders for the transition to ICD-10-CM and PCS coding system that will go into effect on October 1, 2013"--Page 4 of cover.
Unit 1: ICD-9 to ICD-10 -- Unit 2: ICD-10-CM -- Unit 3: ICD-10-PCS -- Unit 4: ICD-10 Planning and Implementation -- Appendixes -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: NOSOLOGY -- CODE NUMBERS